1991
DOI: 10.2166/wst.1991.0434
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sludge Process Response to Variable Inputs of Volatile Organic Contaminants

Abstract: Laboratory-scale activated sludge treatment systems were operated under dynamic loading conditions to investigate the non-steady state behaviour of volatile organic contaminants (VOCs) under controlled conditions. Four step tests were conducted in which an incremental increase in the concentrations of selected contaminants was applied to the reactor feed from background levels of about 15 µg/L to levels of about 100 µg/L for a duration of approximately three hydraulic retention times. Although it was not possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These compound characteristics have been found to contribute to recalcitrant behavior during aerobic biodegradation (Kobayashi andRittmann, 1982, andSahmzyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA et al, 1986). Melcer et al (1991) reported similar behavior for these compounds in bench-scale reactors. The reduced level of biodegradation along with enhanced liquid-gas phase partitioning as indicated by the relatively high Henry's law constants for these compounds likely contributed to the preferential loss by stripping.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…These compound characteristics have been found to contribute to recalcitrant behavior during aerobic biodegradation (Kobayashi andRittmann, 1982, andSahmzyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA et al, 1986). Melcer et al (1991) reported similar behavior for these compounds in bench-scale reactors. The reduced level of biodegradation along with enhanced liquid-gas phase partitioning as indicated by the relatively high Henry's law constants for these compounds likely contributed to the preferential loss by stripping.…”
Section: Resultsmentioning
confidence: 66%
“…The dosing solution was pumped at a rate to attain the target concentration for each compound in the aeration basin influent presented in Table 2. The selection of target concentrations was based upon actual field sampling of raw sewage at different locations in Ontario (Bell et al, 1988, andMelcer et al, 1991). During dosed tapwater and wastewater experiments, the primary effluent was dosed for a period of 26 hours, which represented approximately 4 HRTs of the aeration basin and secondary clarifier, to attain steady-state conditions.…”
Section: Description Of Wastewater Treatment Plants the Behavior Oimentioning
confidence: 99%
“…The above feature of the SBR is attributed to dilution because the retained wastewater comprises~40% of the reactor liquid volume, thus decreasing the ambient concentrations to below inhibition threshold levels. Melcer et al (1991) also reported that changes in influent concentrations of toluene and xylene to an activated sludge system from 15 to 500 p,g/L resulted in a rapid initial increase in effluent concentrations to a peak followed by a decline to a low level close to the original level. observed that doubling of the influent phenol concentration from 500 to I 000 mg/L was attenuated by the system but further increase to 2000 mg/L resulted in system failure.…”
Section: Discussionmentioning
confidence: 96%
“…Data indicated that a relatively long sludge retention time, between 10 and 20 d, was required for maximum removal of PCP, and that a background level of PCP in the influent was required to maintain a PCP degrading population. Further studies using laboratory-scale units with an aeration basin of 5 1 capacity and a clarifier of 4 7 1 capacity were carried out to determine the treatability of variable amounts of volatile organic chemicals including chloroform, tetrachloroethylene, trichlorethane, toluene, xylene, and five heavy metals (Melcer et al, 1991). It was concluded that different mechanisms were responsible for the removal of short-term variable inputs of volatile organic compounds.…”
Section: Continuous Simulation Testsmentioning
confidence: 99%